Analisis Deskriptif Penerapan Sistem Navigasi Peta Pada Video Gim ‘Grand Theft Auto: IV’ - Hariz Kurniawan; Hefi Kristianto; Willy Azrieel; Ressa Priskilla; Viktor Handrianus Pranatawijaya (Bulletin of Computer Science Research, 2024)
Grand Theft Auto IV is one of the groundbreaking installments in the renowned franchise that has shaken up the video game industry. Showcasing the captivating fictional city of Liberty City, the game entices users to explore and immerse themselves in its world. To enhance the immersive experience and facilitate exploration, the game introduces a revolutionary map navigation system. This revolutionary navigation system piqued our interest, leading us to uncover the secrets behind its success in addressing the common navigation issues faced by players over the past decade. This study aims to examine the functionality and application of artificial intelligence within this acclaimed navigation system. Utilizing a descriptive analysis method, we investigated the workings, types, and role of the pathfinding algorithms employed in the map navigation system. The system offers two navigation options, visual and audio, both powered by Dijkstra's algorithm. This algorithm calculates the shortest route between the player’s current position and the set destination. Additionally, the adaptive voice selection algorithm brings the calculated route to life through verbal instructions. In terms of performance, the visual navigation system excels with a route calculation time of 2.064 seconds, while the audio navigation system is slower at 6.009 seconds. Despite this, both navigation systems effectively assist users in navigating the complexities of Liberty City.